CONDUCTOMETRIC METHOD FOR DETERMINING THE CONDUCTIVITY OF POLYELECTROLYTE SOLUTIONS - A.A. Kokoeva; M.B. Begieva; Yu.A. Malkanduev; M.A. Dokshukina (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2019)
A new polymer-based aminoethanoic acid was obtained by the reaction of the radical polymerization. The molar and specific conductivity values of aqueous solutions of the initial amino acid, monomer and polymer were measured by the conductometric method. The results demonstrate the most pronounced electro-conductive properties of the polymer – poly – N, N – diallylamine acid.